Patient-Reported outcomes of pain care research in the adult emergency department: A scoping review. (June 2021) - Wong, Alixandra; Potter, Joseph; Brown, Nathan J; Chu, Kevin; Hughes, James A
Abstract: Despite more than 30 years of research, pain in the emergency department (ED) setting is frequently undertreated. EDs prioritise process measures that often have tenuous links to patient-reported outcomes. However, process measures, such as time to the administration of first analgesic medication, are neither direct objective measures of analgesia nor appropriate surrogate markers of pain relief. Since pain is a subjective symptom that lacks an objective measure, pain research in any clinical environment, including EDs, should rely upon patient-reported outcomes. This scoping review examined patient-reported outcomes (PROs) and patient-reported outcome measures (PROMs) of pain care in the adult emergency department at the micro, meso and macro-level over the last ten years. We reviewed pain care research conducted on adults in EDs over the last ten years and identified 57 articles using 14 patient-reported outcomes of pain care falling into five broad areas, most without validation or adaption to the ED setting. Despite efforts made to incorporate PROs and PROMs into acute pain care research in the ED over the last ten years, there is still no gold-standard PROM in widespread use. We recommend the adaptation of existing tools with rigorous validation in ED populations.